An Exploratory Study on the Impact of Service Quality on Membership Retention in Medical Schemes in South Africa (International Journal of Scientific Research and Management (IJSRM), 2019)
Since the introduction of rice in Uganda in 1904, insufficient information has been generated on quantitative rice postharvest losses in the country. Such inadequate information has partly constrained decision making in developing the rice industry in Uganda. The objective of this study was, therefore, to generate quantitative postharvest losses in two major rice growing hubs of Albertine and Olweny. The AfricaRice postharvest loss assessment procedure was used in the study during the growing seasons of 2015 and 2016. Data was collected at harvesting, threshing, drying and milling stages on 10 rice farms and 10 rice mills in each hub. The most grown “NERICA-4” and “Kaiso, K98” rice varieties both in Oryza Sativa group were used during the study in the Albertine and Olweny hubs respectively. The results indicated that total physical grain losses at aforementioned stages in Albertine and Olweny hubs were 16.8 and 14.1%, respectively. This slight loss variation could be attributed to the different varieties and postharvest practices in these hubs. Losses at harvesting exhibited highest value 6.9 and 5.7% compared to threshing 4.7 and 4.8%; drying 1.8 and 1.4%; and milling 4.8 and 3.5% for Albertine and Olweny hubs respectively. There was no significant difference (p>0.05) discerned in the losses between the hubs. Regardless of the rice hub, significant differences in loss levels (p<0.05) existed along the postharvest operations. These results show that harvesting, threshing and milling were the critical control points in the management of quantitative rice postharvest losses in Uganda.